KONSEP PENGUATAN KEPEMIMPINAN OLEH UMAR BIN ABDUL AZIZ PADA BANI UMAYYAH - Nduru, Friska; NST, Inayatul Sa’adah Athifah; Tariatil (Department of Islamic Education Management, 2025)
Umar bin Abdul Aziz, the eighth caliph of the Umayyad Dynasty, ruled for less than three years but had a significant impact on Islamic history. He is recognized as a just leader who implemented the principles of good governance. This study aims to illustrate his leadership as an inspiration for modern governments in restoring justice, prioritizing the welfare of the people, and improving governance, which is often weakened by power abuse. The research employs a literature review method, gathering relevant theories from various sources, especially scholarly journal articles. It follows a qualitative approach with a descriptive-comparative method, analyzing and scientifically comparing different scholarly perspectives. The findings reveal that Umar bin Abdul Aziz was a devout, integrity-driven leader committed to guiding the Umayyad Dynasty back to the teachings of the Prophet Muhammad and the Rightly Guided Caliphs.